Financial Records Management System for Micro Enterprise - Yeow Xin Yin; Nureize Arbaiy; Jamilah Din (JOIV : International Journal on Informatics Visualization, 2017)
Financial records represent a formal records or written reports of financial activities of an entity to quantify financial performance and financial strength. Most of micro enterprises under Centre for Business and Entrepreneurship (CBER) UTHM is currently using manual records bookkeeping system to keep the financial records. This cause time consuming and human errors. Hence, financial records management system for micro enterprises under CBER is developed. This system is able to simplify invoice records and quotation collection. Financial records management system also can eliminate accounting errors and minimizing records keeping redundancy. The system is developed by using software Brackets, Xampp and PHP programming through agile methodology guide. This system is expected to help micro enterprises to keep track and manage financial records efficiently.